The relationship between cognitive variables and offending behaviour in adults with intellectual disabilities: A systematic review. Issue 4 (20th April 2020) - Hammond, Sarah; Beail, Nigel
Abstract: Background: Interventions for offenders with intellectual disabilities (ID) have used cognitive variables as measures of treatment outcome. However, the relevance of cognitive variables to offending in people with intellectual disabilities is unclear. This review aimed to evaluate the evidence for a relationship between cognitive variables and offending in people with intellectual disabilities. Method: A systematic search identified studies comparing offenders and non‐offenders with intellectual disabilities on an aspect of cognition. Seven cognitive variables were found and compared across 15 studies. These were appraised for their quality using an adapted quality appraisal checklist. The reliability and validity of cognitive measures were also considered. Results and conclusions: Other than for cognitive distortions, the evidence for a relationship between cognitive variables and offending in people with intellectual disabilities is currently limited due to methodological weaknesses and the small number of studies assessing each variable. Clinicians are advised to focus on cognitive distortions until better evidence is available.